EVALUATION OF THYROID FUNCTION MARKERS IN TYPE 2 DIABETIC PATIENTS IN RELATION TO INSULIN RESISTANCE - Othman , Pshtiwan K.; Kakey , Ismail S. (Science Journal of University of Zakho, 2023)
Diabetes mellitus (DM) and thyroid disorders are both caused by endocrine abnormalities, and both have been shown to have a reciprocal influence and frequently coexist. Hence, the current study aims to detect the thyroid functions markers among patients with Type 2 diabetes (T2DM). In this research study, 90 enrolled participants aged 40 to 60 years were taken as samples for the study. There were 66 with T2DM and 24 who were non diabetic healthy individual. All individuals were investigated in terms of age, gender, diabetes duration, glycemic control (HbA1c), fasting blood glucose (FBG), diabetic complications, Body mass index (BMI), waist circumference (WC), and family history of DM. Samples were to assess serum thyroid hormones (TSH, FT3 and FT4), HbA1c, FBG, and insulin levels. The study’s findings showed higher glucose incidence, hyperinsulinemia and higher insulin resistance (IR) in diabetic patients. Additionally, it has been noted that T2DM patients have low TSH concentrations and elevated blood concentrations of FT4 and FT3 than controls. Moreover, there was a highly significant correlation between serum FT4 and FT3 with values of FBG, insulin and IR. Also, a significant association between WC with insulin and Homa – Ir was noted. In conclusion, the diabetic patients showed significant relations with thyroid functions status.